Risco biológico para o circulante de sala operatória - ALMEIDA, André Nunes Gomes de (2009)
Employees of nursing during their work activities in the Surgical Center (SC), are exposed to various occupational hazards, among them biological. The objectives of this study were: to characterize vulnerabilities points to accidents involving biological material for the transient of the operating room (OR), in the trans-operative period and preparation of the Operating Room; to identify the adoption of universal precaution measures, identifying the occurrence of accidents with biological material and to determine the profile of accidents with biological material among circulating OR. Transversal descriptive study conducted with employees of nursing staff engaged in the activity of OR in the SC of a public teaching hospital in the city of Goiânia - GO. Data collection was performed using two instruments: a check list and application of a questionnaire both evaluated and tested. Filling out the checklist was it the first time of data collection that was done by direct observation of the activities of transients in the trans-operative care and dismantling the operating room, including the delivery of the material in the purge of the Centre of Material and Sterilization. Subsequently, a questionnaire was subject to the same observation. We met all the ethical issues for the consideration provided for in resolution 196 of the National Health Council. Data were grouped in tables and figures and descriptive statistics were used for frequency measurements. The data on the perception of transients regarding the observed behaviors were targeted on groups by hierarchical method, cluster analysis. Of the 37 eligible professionals, 30 participated. The majority (93.4%) female, working time in SC, for more than six years (56.6%) and half has another employment relationship, 40.0% with weekly working hours equal or above 60 hours. It was found that 56.6% of circulating never participates in training on biological risk and 34.0% learned the service following colleagues. The vaccine for hepatitis B was referred by 80.0% of workers, 40.0% had anti-HBs. No transient used protection goggles and 53.3% did not use closed shoes while working. Were reported several risk behaviors for exposure to biological material, among which stands out the use of procedure gloves to collect the instruments after surgery, the use of auxiliary table for carrying items such as: instrumental, glass suction, chamber using sharps; collected manually suture needles used in surgery. Disposal of sharps in the OR was predominantly inadequate and no review of the field after surgery occurred in 86.7%. Accidents with biological material were reported by 40.0% of transients, predominantly from percutaneous exposure to blood and only half have been informed about. Behavior characterized in this study, as risk of exposure to biological material, were recognized by circulating OR as present in the daily work, it was possible to observe concordance between both events (high-frequency behavior and high alert as a gift) and disagreement ( high frequency of observation with low alert) with the predominance of agreement. For all behaviors considered as risk of exposure to biological material there was recognition that this occurs. Some behaviors of transient increase the risk to workers from other units of the hospital. The results indicate the need for organizational and administrative changes to the confrontation of the biological risk inherent in the work of the transient of the operating room. Highlighted the need to intensify educational measures regarding the promotion of a safe environment for workers to be frequently reminded that their work exposes them to risks, and risks can be minimized through adherence to standard precautions